Malignant Transformation of BHK(21) Clone 13 Cells by BK Virus—A Human Papovavirus - Major, Eugene O. (1973)
BK virus, a widespread human papovavirus, is shown to cause malignant transformation of BHK(21) clone 13 cells. The transformed cells grow as tumors upon inoculation in adult hamsters. The question of the possible role of this virus in human neoplasia is raised.